(untitled) (Indian Journal of Arid Horticulture, 2021)
Chilli is an important vegetable crop which is grown for green fruits and dry chilli powder as spice. The total production of chilli in India is about 3851 thousand MT in 364 thousand ha area (Anonymous, 2019). India is the largest producer of the chilli in the world followed by China and Pakistan. In India, it has huge demand of green and dry fruits of chilli for aroma, pungency and taste for cooking the vegetables. Biotic factors (sucking pest and soil born diseases) and abiotic factors (temperature, moisture, etc.) are the challenges to the farmers. Therefore, improve nursery raising technique is the only option for regular supply, higher yield and better productivity of chilli to raise healthy, vigorous and disease free especially virus free seedlings. Sharmila et al. (2014) and Chatterjee and Mal (2016) confirm that it also reduce the quantity of the seeds, cost, labour, money, time etc. Pro-tray technology is better for raising seedling, as each seedling grows in cavity allows proper nourishment of seedlings through proper utilization of nutrients; space and sun light (Singh et al., 2010). Soilless media is free from microorganism for raising disease free seedlings (Levnish, 2011). It provides adequate space for each seedling to grow, uniform germination, low quantity of seeds, vigorous and healthy seedling, easy in handling, friendly transportation, better root development and early transplant and establishment into the main field. Keeping these facts in view, present on-farm trail was carried out to compare the method being practiced by the local farmers and the improved method.